Growth and Characterization of Struvite Crystals in Silica Gel Medium and Its Nucleation Reduction Process - SUNDARAMOORTHI, P.; KALAINATHAN, S. (Asian Journal of Chemistry, 2010)
Urinary stone disease is one of the common diseases in the human history. The prevention of urinary stone formation lies in the exact identification of urinary stone constituents. Struvite is one of the frequently occurring constituents of urinary stone due to infection of urinary tract and urine. Struvite crystals were grown by SMS gel technique and effect of sunlight on growth was studied. Characterization studies like XRD, FTIR, TGA/DTA, AAS, SEM and etching were performed and the results analyzed.